2020
DOI: 10.1186/s41072-020-00064-0
|View full text |Cite
|
Sign up to set email alerts
|

Value migration: digitalization of shipping as a mechanism of industry dethronement

Abstract: In this conceptual paper, we review latest developments related to unmanned vessels and sketch potential scenarios that implicate with the existing maritime industry structure. On the one hand, we isolate a range of challenges that make the imminent realization of unmanned vessels seem like a rather utopian pursuit. On the other hand, we explain the reasons that may catalyse their emergence. Inspired by these opposing tensions, we highlight that the digital transformation of the shipping industry has the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…This transformation receives criticism as regards to the way it will affect shipping industry's identity. In this context, automation in the form of unmanned vessels is considered to pose a threat to the identity of the shipping industry as it will be a shift to "non-seafarer-centric shipping" (Poulis et al 2020). Likewise, changes in the nature of work of the seafaring profession and among maritime professionals in general, necessitate the development of new skills related to digital technologies and manifest the importance of lifelong learning.…”
Section: Future Skills and Automation In The Maritime Industrymentioning
confidence: 99%
“…This transformation receives criticism as regards to the way it will affect shipping industry's identity. In this context, automation in the form of unmanned vessels is considered to pose a threat to the identity of the shipping industry as it will be a shift to "non-seafarer-centric shipping" (Poulis et al 2020). Likewise, changes in the nature of work of the seafaring profession and among maritime professionals in general, necessitate the development of new skills related to digital technologies and manifest the importance of lifelong learning.…”
Section: Future Skills and Automation In The Maritime Industrymentioning
confidence: 99%
“…Remote operation/access is currently an intermediate solution when the aim is autonomous CPS but full autonomy cannot be supported (Yagdereli et al, 2015;Höyhtyä et al, 2017). Studies have demonstrated that the digitization in shipping includes productivity gains (Poulis et al, 2020), physical safety (Plaza-Hernández et al, 2021), lower carbon footprints (Larrazabal and Peñas, 2016;Peng et al, 2020), higher efficiency at all levels, lower costs, and flexibility. However, other research shows that there are vulnerabilities in large CPS sensor networks (El-Rewini et al, 2020) and communication systems (e.g., satellite Manulis et al, 2021).…”
Section: Maritime Cyber-securitymentioning
confidence: 99%
“…2.1.1 Digitalization in maritime logistics networks Albeit more slowly than other industries, shipping is also digitally transforming itself by sourcing, adapting, developing and managing industry-specific versions of generic technologies (Lambrou et al, 2019). From a narrow perspective, digitalization or maritime 4.0 can be associated with the vessels providing the shipping service (Sullivan et al, 2020;Poulis et al, 2020). More broadly, digitalization offers many opportunities for both shipping companies and the MLNs they operate within.…”
Section: Digitalization and Value Cocreation In Networkmentioning
confidence: 99%